A conductive and electromagnetic shielding polyaryletherketone-based composite material and a preparation method thereof
By using loaded carbon-based MFI structural molecular sieve and other carbon-type conductive fillers in polyaryletherketone-based composite materials, the problem of poor electromagnetic shielding and mechanical properties of existing composite materials is solved, and the combination of efficient electromagnetic shielding and good mechanical properties is achieved.
Patent Information
- Application Number
- CN202410647649.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-05-23
AI Technical Summary
The electromagnetic shielding and comprehensive mechanical properties of existing polyaryletherketone-based composite materials are poor, making it difficult to meet the demands of electronic equipment for efficient electromagnetic shielding and good mechanical properties.
By loading the carbon-based MFI structure molecular sieve with metal salt, combining other carbon-based conductive fillers with polyaryletherketone for melt blending, extrusion and granulation, conducting and electromagnetically shielded polyaryletherketone composite materials are prepared.
It significantly improves the electromagnetic shielding efficiency and comprehensive mechanical properties of composite materials, can effectively block electromagnetic interference, improve the electromagnetic compatibility of the equipment, and has lower density and good stability, and is suitable for applications in harsh environments.
Smart Images

Figure BDA0004855347970000061 
Figure BDA0004855347970000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a conductive and electromagnetic shielding polyaryletherketone-based composite material and a preparation method thereof. Background Art
[0002] With the development of modern science and technology, electronic devices are increasingly used in our lives. These devices generate a large amount of electromagnetic waves during operation, posing a potential threat to the surrounding environment and human health. Electromagnetic waves are everywhere, and electromagnetic interference is becoming increasingly serious. In order to reduce the impact of electromagnetic waves on the environment and human body, the research and application of conductive or electromagnetic shielding materials is particularly important. Conductive or electromagnetic shielding materials mainly reduce the propagation and interference of electromagnetic waves by absorbing, reflecting and offsetting electromagnetic waves.
[0003] At the same time, as a high-performance thermoplastic resin, polyaryletherketone has good mechanical properties, chemical stability and heat resistance, which makes it widely used in many fields. Polyaryletherketone (PAEK) is a class of thermoplastic resins with excellent performance. Its main chain contains aromatic rings and ketone groups, which give it excellent heat resistance, chemical corrosion resistance and mechanical properties. Polyaryletherketone is compounded with other materials (such as fibers, particles, nanofillers, etc.) to improve its performance, and polyaryletherketone and its composite materials are obtained, which have been widely used in many fields, such as aerospace, automobiles, electronics, medical devices, etc.
[0004] By compounding conductive or electromagnetic shielding materials with polyaryletherketone, polyaryletherketone composite materials with excellent electromagnetic shielding performance can be prepared. This composite material has both the excellent performance of polyaryletherketone and conductive or electromagnetic shielding functions, and has broad application prospects in the fields of electronic equipment, communication equipment, etc. However, the electromagnetic shielding and comprehensive mechanical properties of existing composite materials are not good. Summary of the invention
[0005] The present invention provides a conductive and electromagnetic shielding polyaryletherketone-based composite material and a preparation method thereof in order to improve the electromagnetic shielding and comprehensive mechanical properties of the composite material. The composite material of the present invention has significant electromagnetic shielding effectiveness and excellent comprehensive mechanical properties.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A method for preparing a conductive and electromagnetically shielding polyaryletherketone-based composite material comprises the following steps:
[0008] S1, forming a mixed dispersion of a carbon-based MFI structure molecular sieve and a metal salt, heating the mixture for reaction, and subsequently calcining the mixture to obtain a supported carbon-based MFI structure molecular sieve;
[0009] The metal loading amount in the supported carbon-based MFI structure molecular sieve is in the range of 2wt%-15wt%;
[0010] S2, after uniformly mixing the supported carbon-based MFI structure molecular sieve and polyaryletherketone, melt blending, extrusion and granulation are performed to obtain a first material;
[0011] S3, after uniformly mixing the conductive filler and the polyaryletherketone, melt blending, extrusion and granulation are performed to obtain a second material;
[0012] S4. Mix the first material and the second material according to a proportion, melt-blend, extrude or granulate to obtain a conductive and electromagnetic shielding polyaryletherketone-based composite material.
[0013] Furthermore, the method for obtaining the carbon-based MFI structure molecular sieve is: using a water-soluble biomass carbon source as a precursor, using carbonate as an activator, selecting a quaternary ammonium salt as a template, after forming a reaction system, adjusting the pH to alkaline for hydrothermal reaction to obtain a product, carbonizing the product, washing it, and drying it to obtain the carbon-based MFI structure molecular sieve.
[0014] Furthermore, the water-soluble biomass carbon source is selected from one or more of sugars, alcohols, phenols, carboxylic acids, and proteins; the carbonate is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate; the quaternary ammonium salt is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, tetraoctylammonium hydroxide, and tetradecylammonium hydroxide.
[0015] Furthermore, the molar ratio of the water-soluble biomass carbon source, the carbonate and the quaternary ammonium salt is 0.25-0.5: 0.35-0.4 mol: 0.05-0.08 mol; the amount of solvent in the reaction system is 1.5 to 3.5 times the weight of the total material; the pH is adjusted to alkaline to adjust the pH value of the reaction system to 9.5-10.5; the temperature of the hydrothermal reaction is 140-160°C and the reaction time is 18-36h; the carbonization treatment is a heat treatment at 850-1100°C for 1-3h under nitrogen protection.
[0016] Furthermore, the conductive filler is selected from one or more of carbon black, graphite, graphene, carbon fiber, carbon nanotubes, metal or its oxide; the polyaryletherketone is selected from one or more of polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK); the metal salt is a nitrate, and the metal therein is selected from one or more of cobalt, chromium, copper, iron, nickel, silver, rare earth metals, zinc, vanadium, titanium, manganese, aluminum, indium, tin and antimony.
[0017] Furthermore, the mass molar ratio of the carbon-based MFI structure molecular sieve and the metal salt is 4g:0.001-0.01mol; the mass concentration of the carbon-based MFI structure molecular sieve in the mixed dispersion is 15-25%; the temperature of the heating reaction is 75-90°C and the reaction time is 1-3h; the temperature of the calcination is 400-600°C and the calcination time is 2-5h.
[0018] Furthermore, in the composite material, based on 100wt%, it contains 5-20wt% of the supported carbon-based MFI structured molecular sieve, 0.5-15% of the conductive filler, and the balance is the polyaryletherketone.
[0019] Another aspect of the present invention provides a conductive and electromagnetically shielding polyaryletherketone-based composite material obtained by the above preparation method.
[0020] Beneficial technical effects: The present invention uses water-soluble biomass as a carbon source, adopts a quaternary ammonium salt template method to prepare a carbon-based MFI structured molecular sieve, loads it with metals or their oxides, and uses other carbon conductive materials as fillers to prepare a polyaryletherketone-based composite material; the prepared composite material has significant electromagnetic shielding effectiveness, can effectively block the electromagnetic interference generated by electronic equipment, and improve the electromagnetic compatibility of the equipment; compared with traditional metal shielding materials, the composite material made of carbon-based MFI structured molecular sieve has a lower density, which helps to achieve lightweight design, and the carbon-based MFI structured molecular sieve has good stability under high temperature, high pressure and chemical corrosion environments, and is suitable for electromagnetic shielding under harsh environmental conditions. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0023] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0024] Example 1
[0025] A method for preparing a conductive and electromagnetically shielding polyaryletherketone-based composite material comprises the following steps:
[0026] S1. Preparation of carbon-based MFI molecular sieve: 100 g (0.29 mol) sucrose and 50 g (0.36 mol) K 2 CO 3 Mix well in deionized water, add 20 grams of tetrapropylammonium hydroxide solution (10wt% aqueous solution), the total amount of water in the system is 500g, adjust the pH of the reaction system to 10, mix well, place at 150°C for hydrothermal reaction for 24 hours, filter to obtain the product after the reaction is completed, dry and heat to 900°C at a uniform rate under nitrogen protection and perform carbonization treatment at this temperature for 2 hours, wash the product after carbonization with deionized water to neutrality, and then dry at 110°C for 12 hours, and subsequent washing and drying can remove the remaining template and activator to obtain 120g of carbon-based MFI structure molecular sieve, which has a particle size of 0.2μm and a pore size of 0.55-0.6nm after testing;
[0027] Preparation of supported carbon-based MFI structure molecular sieve: 100g of carbon-based MFI structure molecular sieve and 200g of cobalt nitrate solution (concentration 0.1mol / L) are formed into a mixed dispersion, stirred and reacted at 80°C for 2 hours, filtered after the reaction is completed and washed with deionized water until no metal ions are detected, dried at 100°C for 12 hours, and calcined in air at 450°C for 3 hours to obtain Co-supported carbon-based MFI structure molecular sieve (due to the inevitable errors in the preparation process of each batch and the differences in particle size and pore size of each batch of carbon-based MFI structure molecular sieves, the Co loading fluctuates within the range of about 3-7wt%);
[0028] S2, after uniformly mixing 20 g of the Co-supported carbon-based MFI structured molecular sieve and 200 g of polyetheretherketone, melt-blending, extruding and granulating at 320-380° C., to obtain a first material;
[0029] S3, after evenly mixing 5 g of carbon nanotubes (tube diameter 7-15 nm, aspect ratio>400) and 100 g of polyetheretherketone, melt blending, extruding and granulating at 320-380° C., to obtain a second material;
[0030] S4. After uniformly mixing the first material and the second material in a mass ratio of 3:1, melt-blending is performed at 320-380° C., and extrusion granulation is performed to obtain a conductive and electromagnetic shielding polyaryletherketone-based composite material.
[0031] The composite material in this case is calculated based on 100wt%, of which the Co-loaded carbon-based MFI structured molecular sieve accounts for about 7.8%, the carbon nanotubes account for about 0.6%, and the balance is PEEK.
[0032] Example 2
[0033] A method for preparing a conductive and electromagnetically shielding polyaryletherketone-based composite material comprises the following steps:
[0034] S1. Preparation of carbon-based MFI molecular sieve: 63.1 g (0.35 mol) of glucose and 42.5 g (0.4 mol) of Na 2 CO 3 Mix well in deionized water, add 20 grams of tetrabutylammonium hydroxide solution (40wt% aqueous solution), the total amount of water is 380g, adjust the pH of the reaction system to 10.2, mix well, place at 140°C for hydrothermal reaction for 36 hours, filter to obtain the product after the reaction is completed, dry and heat to 1000°C at a uniform rate under nitrogen protection and perform carbonization treatment at this temperature for 2 hours, wash the product after carbonization with deionized water to neutrality, and then dry at 110°C for 12 hours, and subsequent washing and drying can remove the remaining template and activator to obtain 70g of carbon-based MFI structure molecular sieve, which has a particle size of 0.2μm and a pore size of 0.55-0.6nm after testing;
[0035] Preparation of supported carbon-based MFI structure molecular sieve: 100g of carbon-based MFI structure molecular sieve and 200g of a mixed solution containing cobalt nitrate and ferric nitrate (cobalt concentration 0.1mol / L, iron concentration 0.1mol / L) are formed into a mixed dispersion, stirred and reacted at 85°C for 2.5 hours, filtered after the reaction is completed and washed with deionized water until no metal ions are detected, dried at 100°C for 12 hours, and calcined in air at 500°C for 2.5 hours to obtain Co / Fe co-supported carbon-based MFI structure molecular sieve (due to the inevitable errors in the preparation process of each batch and the differences in particle size and pore size of each batch of carbon-based MFI structure molecular sieves, the total loading of Co and Fe is in the range of 4-7wt%);
[0036] S2, after uniformly mixing 50 g of the Co / Fe co-loaded carbon-based MFI structured molecular sieve and 200 g of polyetheretherketone, melt blending, extrusion and granulation are performed at 320-380° C. to obtain a first material;
[0037] S3, after uniformly mixing 10 g of carbon fiber (diameter 5-10 μm, aspect ratio>100) and 100 g of polyetheretherketone, melt blending, extrusion and granulation are performed at 320-380° C. to obtain a second material;
[0038] S4. After uniformly mixing the first material and the second material in a mass ratio of 1:1, melt-blending is performed at 320-380° C., and extrusion granulation is performed to obtain a conductive and electromagnetic shielding polyaryletherketone-based composite material.
[0039] The composite material in this case is calculated based on 100wt%, of which the Co / Fe co-loaded carbon-based MFI structured molecular sieve accounts for about 13.9%, the carbon fiber accounts for about 2.7%, and the balance is PEEK.
[0040] Example 3
[0041] A method for preparing a conductive and electromagnetically shielding polyaryletherketone-based composite material comprises the following steps:
[0042] S1. Preparation of carbon-based MFI molecular sieve: 86.5 g (0.45 mol) of citric acid and 52.5 g (0.38 mol) of K 2 CO 3 Mix well in deionized water, add 25 grams of tetraoctyl ammonium hydroxide solution (20wt% methanol solution), the total amount of water is 450g, adjust the pH of the reaction system to 9.8, mix well, place at 155°C for hydrothermal reaction for 24 hours, filter to obtain the product after the reaction is completed, dry and heat to 950°C at a uniform rate under nitrogen protection and perform carbonization treatment at this temperature for 2 hours, wash the product after carbonization with deionized water to neutrality, and then dry at 110°C for 12 hours, and subsequent washing and drying can remove the remaining template and activator to obtain 130g of carbon-based MFI structure molecular sieve, which has a particle size of 0.1-0.2μm and a pore size of 0.4-0.5nm after testing;
[0043] Preparation of supported carbon-based MFI structure molecular sieve: 100g of carbon-based MFI structure molecular sieve and 200g of a mixed solution containing cobalt nitrate, nickel nitrate and copper nitrate (cobalt concentration 0.1mol / L, nickel concentration 0.1mol / L, copper concentration 0.1mol / L) are formed into a mixed dispersion, and stirred at 80°C for 3 hours. After the reaction is completed, the mixture is filtered and washed with deionized water until no metal ions are detected, dried at 100°C for 12 hours, and calcined in air at 450°C for 2 hours to obtain Co / Ni / Cu co-supported carbon-based MFI structure molecular sieve (due to the inevitable errors in the preparation process of each batch and the differences in particle size and pore size of the carbon-based MFI structure molecular sieve prepared in each batch, the total loading amount of Co, Ni and Cu is within the range of 10-15wt%);
[0044] S2, after uniformly mixing 60 g of the Co / Ni / Fe co-loaded carbon-based MFI structured molecular sieve and 200 g of polyetheretherketone, melt blending, extrusion and granulation are performed at 320-380° C. to obtain a first material;
[0045] S3, after uniformly mixing 40 g of graphene (sheet diameter 0.5-2 μm) and 100 g of polyetheretherketone, melt blending, extrusion and granulation are performed at 320-380° C. to obtain a second material;
[0046] S4. After uniformly mixing the first material and the second material in a mass ratio of 1:1, melt-blending is performed at 320-380° C., and extrusion granulation is performed to obtain a conductive and electromagnetic shielding polyaryletherketone-based composite material.
[0047] The composite material in this case is calculated based on 100wt%, of which the Co / Fe co-loaded carbon-based MFI structured molecular sieve accounts for about 15%, graphene accounts for about 10%, and the balance is PEEK.
[0048] Comparative Example 1
[0049] The preparation process of the composite material in this case is the same as that of Example 1, except that no carbon nanotubes are added (i.e. no S3) and no Co is loaded. The obtained composite material is calculated based on 100wt%, of which the carbon-based MFI structured molecular sieve accounts for about 8.5% and the remainder is PEEK.
[0050] Comparative Example 2
[0051] The preparation process of the composite material in this case is the same as that of Example 1, except that no carbon nanotubes are added (i.e. no S3). The obtained composite material is calculated based on 100wt%, of which the Co-loaded carbon-based MFI structured molecular sieve accounts for about 8.5% and the remainder is PEEK.
[0052] Comparative Example 3
[0053] The preparation process of the composite material in this case is the same as that of Example 1, except that the carbon-based MFI structured molecular sieve is not loaded.
[0054] Comparative Example 4
[0055] The preparation process of the composite material in this case is the same as that of Example 1, except that only S3 is used. The obtained composite material is calculated based on 100wt%, of which carbon nanotubes account for about 8.5% and the remainder is PEEK.
[0056] Comparative Example 5
[0057] The preparation process of the composite material in this case is the same as that of Example 1, except that porous carbon (pore size 2-50 nm, particle size 10 μm-50 μm) is used as the matrix to load Co metal.
[0058] Test Case
[0059] The above cases were tested for performance, and the results are shown in Table 1.
[0060] Table 1 Composite material properties of each case
[0061]
[0062]
[0063] (Note: The sample for volume resistance test is a disc with a diameter of 100 mm and a thickness of 1 mm)
[0064] Comparative Example 1 only uses carbon-based MFI molecular sieves and PEEK for compounding, Comparative Example 2 uses carbon-based MFI molecular sieves loaded with Co for compounding with PEEK, Comparative Example 3 uses carbon nanotubes and carbon-based MFI molecular sieves and PEEK for compounding, and Comparative Example 4 only uses carbon nanotubes and PEEK for compounding, which are not good for improving electromagnetic shielding performance, mechanical properties and conductive properties. After the loaded carbon-based MFI molecular sieve is compounded with other carbon conductive fillers in PEEK, the improvement of electromagnetic shielding performance, mechanical properties and conductive properties has achieved good technical effects. Comparative Example 5 uses other carriers to load Co. Although the electromagnetic shielding performance and conductive properties are comparable to those of Example 1, the mechanical properties are worse than those of Example 1. The composite material obtained by the method of the present invention has good conductive properties and electromagnetic shielding properties while ensuring that the material has good mechanical properties.
[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a conductive and electromagnetic shielding polyaryletherketone-based composite material, characterized in that: The steps include: S1, forming a mixed dispersion of a carbon-based MFI structure molecular sieve and a metal salt, heating the mixture for reaction, and subsequently calcining the mixture to obtain a supported carbon-based MFI structure molecular sieve; The method for obtaining the carbon-based MFI structure molecular sieve is as follows: using a water-soluble biomass carbon source as a precursor, using a carbonate as an activator, selecting a quaternary ammonium salt as a template agent, forming a reaction system, adjusting the pH to alkaline for hydrothermal reaction to obtain a product, carbonizing the product, washing it, and drying it to obtain the carbon-based MFI structure molecular sieve; The water-soluble biomass carbon source is selected from one or more of sugars, alcohols, fatty acids, and protein compounds; the carbonate is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate; the quaternary ammonium salt is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, tetraoctylammonium hydroxide, and tetradecylammonium hydroxide; The molar ratio of the water-soluble biomass carbon source, the carbonate and the quaternary ammonium salt is 0.25-0.35 mol: 0.35-0.4 mol: 0.005-0.05 mol; the amount of the solvent in the reaction system is 1.5 to 3.5 times the weight of the total material; the pH is adjusted to be alkaline to adjust the pH value of the reaction system to 9.5-10.5; the temperature of the hydrothermal reaction is 140-160° C. and the reaction time is 18-36 h; the carbonization treatment is heat treated at 850-1100° C. for 1-3 h under nitrogen protection; The metal loading amount in the supported carbon-based MFI structured molecular sieve is in the range of 2wt%-15wt%; S2, after uniformly mixing the supported carbon-based MFI structure molecular sieve and polyaryletherketone, melt blending, extrusion and granulation are performed to obtain a first material; S3, after uniformly mixing the conductive filler and the polyaryletherketone, melt blending, extrusion and granulation are performed to obtain a second material; S4, mixing the first material and the second material according to a proportion, melt blending, extruding or granulating to obtain a conductive and electromagnetic shielding polyaryletherketone-based composite material; In the composite material, based on 100wt%, it contains 5-20wt% of the supported carbon-based MFI structure molecular sieve, 0.5-15wt% of the conductive filler, and the balance is the polyaryletherketone.
2. The method for preparing a conductive and electromagnetic shielding polyaryletherketone-based composite material according to claim 1, characterized in that: The conductive filler is selected from one or more of carbon black, graphite, graphene, carbon fiber, carbon nanotubes, metal or its oxide; the polyaryletherketone is selected from one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone and polyetherketoneetherketoneketone; the metal salt is a nitrate, and the metal in the nitrate is selected from one or more of cobalt, chromium, copper, iron, nickel, silver, rare earth metals, zinc, vanadium, titanium, manganese, aluminum, indium, tin and antimony.
3. The method for preparing a conductive and electromagnetic shielding polyaryletherketone-based composite material according to claim 1, characterized in that: The mass molar ratio of the carbon-based MFI structure molecular sieve and the metal salt is 4g:0.001-0.01mol; the mass concentration of the carbon-based MFI structure molecular sieve in the mixed dispersion is 15-25%; the temperature of the heating reaction is 75-90°C and the reaction time is 1-3h; the temperature of the calcination is 400-600°C and the calcination time is 2-5h.
4. A conductive and electromagnetic shielding polyaryletherketone-based composite material obtained according to the preparation method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Polyetheretherketone-base composite electromagnetic shielding material and preparation method thereof
CN102321338A
Preparation method of nano metal loaded molecular sieve based catalyst
CN103272634A
Polymer electromagnetic shielding composite material with multilayer foam structure and preparation method thereof
CN111660641A